Time trends of chronic HBV infection over prior decades – A global analysis - Ott, Jördis J.; Horn, Johannes; Krause, Gérard; Mikolajczyk, Rafael T. (Journal of hepatology, 2017)
[Display omitted] Information on trends in chronic hepatitis B virus (HBV) prevalence across countries is lacking. We studied changes in chronic HBV infection over previous decades by country, and assessed patterns of change between and within WHO-defined regions. Based on data from a published systematic review on chronic HBV, we applied a linear model on the logit scale to assess time trends in country-specific prevalence. Estimated HBsAg prevalence in 2000 and relative changes in prevalence over time were evaluated by country and region. Sufficient data were available for 50 countries, mostly showing reductions in prevalence over time. Various degrees of heterogeneity were observed within regions, with a relatively homogenous pattern in the Eastern Mediterranean region with strong decreases in HBsAg prevalence. Europe showed a mixed pattern: higher and stable chronic HBsAg prevalence in Eastern, and constantly low prevalence in Western Europe. In Africa, some countries demonstrated no change in prevalence; increases were seen in Uganda (odds ratio 1.05 per year; 95% confidence interval 1.04–1.06), Nigeria (1.02; 1.02–1.02), Senegal (1.01; 1.01–1.02), and South Africa (1.02; 1.01–1.02). With some exceptions, country-patterns overlapped among countries of South East Asian and Western Pacific regions, characterized by low-medium HBsAg decreases, most prominent in China and Malaysia. Most countries experienced decreases in HBsAg prevalence. Dynamics varied, even within regions; decreases occurred mostly before the direct effects of childhood vaccination may have manifested. These findings together with stable and increasing HBsAg prevalence in some countries of Africa and Eastern Europe indicate the need for further tailored country-specific prevention. This study investigated time trends in prevalence of chronic HBV infection in 50 countries worldwide over the last decade, by estimating relative changes in prevalence. Results show decreases in chronic HBV infection in most countries; no changes or increases in prevalence are noted in some African countries. Reasons for time changes need to be investigated further; based on the results, various prevention measures have contributed to reductions, and further tailored HBV prevention is required to combat the disease on a global level.